Discontinuation of Initial Antiretroviral Therapy in Clinical Practice: Moving Toward Individualized Therapy. (1st March 2016) - Di Biagio, Antonio; Cozzi-Lepri, Alessandro; Prinapori, Roberta; Angarano, Gioacchino; Gori, Andrea; Quirino, Tiziana; De Luca, Andrea; Costantini, Andrea; Mussini, Cristina; Rizzardini, Giuliano; Castagna, Antonella; Antinori, Andrea; et al.
Abstract : Background: Study aim was to estimate the rate and identify predictors of discontinuation of first combination antiretroviral therapy (cART) in recent years. Methods: Patients who initiated first cART between January 2008 and October 2014 were included. Discontinuation was defined as stop of at least 1 drug of the regimen, regardless of the reason. All causes of discontinuation were evaluated and 3 main endpoints were considered: toxicity, intolerance, and simplification. Predictors of discontinuation were examined separately for all 3 endpoints. Kaplan–Meier analysis was used for the outcome discontinuation of ≥1 drug regardless of the reason. Cox regression analysis was used to identify factors associated with treatment discontinuation because of the 3 reasons considered. Results: A total of 4052 patients were included. Main reason for stopping at least 1 drug were simplification (29%), intolerance (21%), toxicity (19%), other causes (18%), failure (8%), planned discontinuation (4%), and nonadherence (2%). In a multivariable Cox model, predictors of discontinuation for simplification were heterosexual transmission ( P = 0.007), being immigrant ( P = 0.017), higher nadir lymphocyte T CD4 + cell ( P = 0.011), and higher lymphocyte T CD8 + cell count ( P = 0.025); for discontinuation due to intolerance: the use of statins ( P = 0.029), higher blood glucose levels ( P = 0.050). About toxicity: higher blood glucose levels ( P = 0.010) and the use of zidovudine/lamivudine as backbone ( P = 0.044). Conclusions: In the late cART era, the main reason for stopping the initial regimen is simplification. This scenario reflects the changes in recommendations aimed to enhance adherence and quality of life, and minimize drug toxicity. Abstract : Supplemental Digital Content is Available in the Text.